OPTIMALISASI SUMBER DAYA MANUSIA DALAM PENYELENGGARAAN ADMINISTRASI PERTANAHAN - Andrianto Andrianto; Muliyadi Hamid; Sri Adrianti Muin (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the conditions and constraints of human resource optimization in the implementation of land administration and to formulate the necessary efforts to improve the quality of land administration services in four urban villages in Tanjung Palas District, Bulungan Regency. The research employed a qualitative approach based on the interpretive paradigm. Data were collected through in-depth interviews, observation, documentation, and the Community Satisfaction Survey (CSS) involving village heads, heads of government affairs, and land administration staff. Data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation, member checking, and peer debriefing. The findings reveal that the optimization of human resources in the implementation of land administration in the four urban villages has not yet been fully achieved. This condition is attributed to the insufficient number of implementing personnel based on the staffing map, the imbalance of workload among employees, task assignments that are not fully aligned with the competencies and experience of the staff, and the limited administrative support system. To improve the quality of land administration services, several strategic measures are recommended, including the preparation of a Workload Analysis (WLA), updating the staffing map, establishing Standard Operating Procedures (SOPs) for land administration, conducting regular technical training, developing a digital-based land administration system, and strengthening coordination and monitoring. The implementation of these measures is expected to enhance the effectiveness, efficiency, accountability, and overall quality of land administration services while improving public-oriented service delivery.